2022
DOI: 10.1111/hir.12424
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and facilitators of implementing an information system for health grey literature in Iran: Experts’ views and perspectives

Abstract: Background: Despite the importance of health grey literature, there is not a comprehensive information system for managing these valuable resources in Iran. Objectives:This study aimed at identifying the barriers to and facilitators of implementing a comprehensive national information system for health grey literature. Material and method:This study applied the qualitative research method.Semi-structured interviews were conducted among 19 experts in related fields. A qualitative content analysis was used to an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…In the second phase, participants were asked to identify the people with whom they had the most collaboration during the programmes and projects in the form of municipal service providers, university researchers and psychologists who assisted them in those activities as the participants of the second stage (Group B). In general, the participants were individuals who had previous specialised knowledge of the research topic (Mirzaei et al 2022). Participants' information is provided in Table 1.…”
Section: Description Of the Study Areamentioning
confidence: 99%
“…In the second phase, participants were asked to identify the people with whom they had the most collaboration during the programmes and projects in the form of municipal service providers, university researchers and psychologists who assisted them in those activities as the participants of the second stage (Group B). In general, the participants were individuals who had previous specialised knowledge of the research topic (Mirzaei et al 2022). Participants' information is provided in Table 1.…”
Section: Description Of the Study Areamentioning
confidence: 99%
“…While library jargon was identified as a potential barrier by Urquhart & Brettle, issues of content management and data integration were identified as possible impediments in the design and implementation of a national information system for health grey literature in Iran (Mirzaei et al 2022). However, Mirzaei et al also identified multiple facilitators for such a national service including documented policies and strict quality control.…”
mentioning
confidence: 99%